CONTRIBUTION OF ACADEMIC SELF-CONCEPT, STUDENT DISCIPLINE AND LEARNING MOTIVATION TO STUDENTS' MATHEMATICS LEARNING OUTCOMES - Suardiani, Ni Putu; Ardana, I Made; Suastika, I Nengah (Pena Cendekia Insani, 2026)
This study aims to describe and analyze the contribution of variables: (1) academic self-concept, (2) student discipline, (3) learning motivation, and (4) academic self-concept, student discipline, and learning motivation both simultaneously to the learning outcomes of Mathematics students in grade V of SDN Cluster II, Abiansemal District, Badung Regency. The sample in this study amounted to 124 students. The sample determination technique uses probability sampling/random sampling techniques. This research was designed in the form of ex post facto research. Data were collected using questionnaires on academic self-concept, student discipline, learning motivation and learning outcome documents. The data were analyzed by simple and multiple linear regression. Research results: (1) academic self-concept makes a positive and significant contribution to Mathematics learning outcomes with a regression coefficient of 0.449; (2) student discipline makes a positive and significant contribution to Mathematics learning outcomes with a regression coefficient of 0.379; (3) learning motivation makes a positive and significant contribution to Mathematics learning outcomes with a regression coefficient of 0.540; and (4) simultaneously, academic self-concept, student discipline, and learning motivation make a significant contribution to Mathematics learning outcomes with a determination coefficient of 96.6%, while the remaining 3.4% is influenced by other factors outside the research model. Based on these findings, it can be concluded that academic self-concept, student discipline, and learning motivation are factors that significantly contribute to Mathematics learning outcomes.